2004
DOI: 10.1103/physreva.69.053616
|View full text |Cite
|
Sign up to set email alerts
|

Quench dynamics across quantum critical points

Abstract: We study the quantum dynamics of a number of model systems as their coupling constants are changed rapidly across a quantum critical point. The primary motivation is provided by the recent experiments of Greiner et al. (Nature 415, 39 (2002)) who studied the response of a Mott insulator of ultracold atoms in an optical lattice to a strong potential gradient. In a previous work (cond-mat/0205169), it had been argued that the resonant response observed at a critical potential gradient could be understood by prox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
352
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(373 citation statements)
references
References 11 publications
(26 reference statements)
20
352
1
Order By: Relevance
“…We discuss the effective "generic" thermalization induced by integrability breaking, by analyzing the changes in the space asymptotics of the order parameter correlators, after a quench in the transverse-field strength Γ: as discussed in Sec. IV B, for quenches crossing the Ising quantum critical point from the paramagnetic to the ferromagnetic side, non-thermal sinusoidal oscillations in real space naturally emerge 15,52 . Below we numerically show that a non-integrable perturbation leads to a suppression of them, thus driving the system towards a completely thermal-like behavior, where only the exponential decay in space of correlations is present.…”
Section: Sensitivity To the Breaking Of Integrabilitymentioning
confidence: 99%
“…We discuss the effective "generic" thermalization induced by integrability breaking, by analyzing the changes in the space asymptotics of the order parameter correlators, after a quench in the transverse-field strength Γ: as discussed in Sec. IV B, for quenches crossing the Ising quantum critical point from the paramagnetic to the ferromagnetic side, non-thermal sinusoidal oscillations in real space naturally emerge 15,52 . Below we numerically show that a non-integrable perturbation leads to a suppression of them, thus driving the system towards a completely thermal-like behavior, where only the exponential decay in space of correlations is present.…”
Section: Sensitivity To the Breaking Of Integrabilitymentioning
confidence: 99%
“…7) with H a block circulant matrix (apart from boundary terms), that is to say 1.7)). The dimension d of the blocks depends on the spin interaction.…”
Section: Quenches In Noninteracting Spin Chainsmentioning
confidence: 99%
“…Recently, Sengupta et al [14] have studied time evolution of the Ising order correlations under a time-dependent transverse field and shown that the order parameter is best enhanced in the vicinity of the quantum critical point. Quan et al [15] have studied transition dynamics of a quantum two-level system from a pure state to a mixed one induced by the quantum criticality of the surrounding many-body system.…”
mentioning
confidence: 99%